ANALISIS PENGARUH KUALITAS KOMUNIKASI PEMASARAN DAN ELEMEN MEREK TERHADAP EKUITAS MEREK DENGAN KESADARAN MEREK SEBAGAI VARIABEL INTERVENING (STUDI KASUS PRODUK LIPSTIK MEREK RED-A) - Septyani, Rizky (Diponegoro Journal of Management, 2016)
Red lipstick-A is one of the variants of cosmetics production in PT. Vitapharm. Red-A lipstick product became one of the local name can be in the estimate in Indonesia are cosmetic. However, intense competition make the lipstick Red-A brand value index decreased the mean performance degradation occurs on the brand. It is characterized by a decline in Satisfaction, and Brand Share. As one brand that has been widely known and taken into account the Red-A need to be careful because it is an indication of the decline of Red lipstick product interests-A. This research aims to know the influence of the quality of Marketing CommunicationÂ  and elements of the Brand against brand equity with brand awareness as Intervining variable.This research uses 4 variables i.e. marketing communications, brand equity, Brand Elements, and brand awareness. Hypothesis testing studies use data as much as 100 respondents. Analytical techniques used in this research is a Structural Equation Models (SEM) of AMOS 22.0.From the results of research to know that the quality of influential marketing communications in a positive but not significant toward brand awareness, brand elements are positive and significant effect against the brand awareness and ultimately brand awareness will effect positively and significantly to Red-A lipstick brand equity.